GAMBARAN INTENSI PENYEBARAN MATERI PORNOGRAFI ORANG LAIN TANPA PERSETUJUAN PADA REMAJA LAKI-LAKI - Gabriella Alika Rayna Soetopo; Patricia Lidwina Alvionita Kristianti; Theresia Bintang Kusuma; Victoria Puteri Arista (MANASA, 2020)
Non-consensual forwarding of sexts is a form of online sexual harassment. This behavior is often foundduring teenage years up to young adults. The impacts to the victim are reputational damage, a feelingof violated, and a possible emergence of trauma. This research aims to describe the intention of nonconsensual forwarding of sexts using the theory of planned behavior as the theoretical framework. Theapproach implemented in this research was qualitative design using thematic analysis. Participantsinvolved in this study are 4 male teenagers. The data collection method used is a semi-structured onlineinterview. The findings showed that non-consensual forwarding of sexts as the result of attitude towardsthe behavior, perceived norms, and self-efficacy. On the one hand, this behavior is regarded as wrongand should not be done. On the other hand, it is rated as a positive behavior since it brings satisfactionto the individual. The biggest driving force is the subjective norms perceived among their peer group.Their peer groups were not only refrain from punishing this behavior, but also encouraged this.Therefore, non-consensual forwarding of sexts is deemed to be easier when done with trusted peoplelike close friends. Even so, there is still the fear of getting caught by others, especially the victims.